Efficacy and Safety of a Bovine-Associated Staphylococcus aureus Phage Cocktail in a Murine Model of Mastitis - Breyne, Koen; Honaker, Ryan W.; Hobbs, Zachary; Richter, Manuela; Żaczek, Maciej; Spangler, Taylor; Steenbrugge, Jonas; Lu, Rebecca; Kinkhabwala, Anika; Marchon, Bruno; Meyer, Evelyne; Mokres, Lucia (Frontiers in Microbiology, 2017)
Overuse of antibiotics is a major problem in the treatment of bovine mastitis, and antibiotic treatment is frequently non-curative, thus alternative treatments are necessary. The primary aim of this study was to evaluate the efficacy of a purified phage cocktail for treatment of bovine Staphylococcus aureus mastitis in a well-defined mouse model. Candidate phages were selected based on their in vitro performance and subsequently processed into an optimally composed phage cocktail. The highest scoring phages were further tested for efficacy and resistance suppression in broth and raw milk, with and without supplemental IgG. As these in vitro results displayed significant decreases in CFU, the cocktail was purified for testing in vivo. Lactating mice were intramammarily inoculated with S. aureus N305 (ATCC 29740), a clinical bovine mastitis isolate commonly used for experimental infection of dairy cows. The phage cocktail was applied via the same route four hours post-inoculation. Treated mammary glands were graded for gross pathological appearance and excised for bacterial and phage load quantification as well as histopathology. Observation of gross macroscopic and histopathological changes and CFU quantification demonstrated that the phage cocktail treatment significantly improved mastitis pathology and decreased bacterial counts. Phage PFU quantification indicated that the tested phage cocktail treatment was able to maintain high intramammary phage titers without spreading systemically. The in vivo results complement the in vitro data and support our concept of phage therapy as an innovative alternative or supplementation therapy to antibiotics for the treatment of bovine mastitis.